Child and adolescent psychotherapy and psychoanalysis : one hundred years after 'Little Hans' - Baker, Karen E.; Brandell, Jerrold R. (London ; New York : Routledge, 2013)
This book introduces the single use of four widely-used qualitative approaches and then introduces ways and applications of using the approaches in combination. Personal insight into qualitative research practice from each of the contributors covers health psychology, social psychology, criminal psychology, gender studies psychotherapy, counselling psychology and organizational psychology.
Contributors Acknowledgements Part 1: Some Core Approaches Qualitative Research in Psychology Grounded Theory Approaches Interpretative Phenomenological Analysis Discourse Analysis Approaches Narrative Analysis Approaches Part 2: Combining Core Approaches Pragmatics of Pluralistic Qualitative Research Interpreting Data Pluralistically Writing Up Pluralistic Qualitative Research Looking Forward Glossary References Index
Includes Bibliographic References and Index
PSYCH
Keywords: Child psychotherapy; Adolescent psychotherapy; Child analysis